Development of a Capillary Electrophoresis Chip with Integrated Electrochemical Sensors (International Journal of Automation and Smart Technology, 2025)
Capillary electrophoresis (CE) chips with amperometric integration offers improved portability, high detection throughput, small sample and reagent volumes, low driving voltages and sample injection and separation. This article reviews recent CE chip developments and applications in the integration of amperometric sensors. We describe the development of three different configurations (in-channel, off-channel and end-channel). CE chips with integrated EC detectors have great promise in applications including diagnostics, environmental monitoring and biological assays.